(untitled) (International Journal of Engineering Sciences & Management Research, 2015)
The Deaf people have difficulty in communicating with others like who don’t understand sign language. In this purpose we are implementing this research. There has been a great development in the past few years on the infusion of technology in the life and curriculum of people with special needs. A techno logy that enables an individual with a learning disability to compensate for specific deficits is indeed an assistive technology. Technology to incorporate would usually range between the simple low-level technologies to the robust emerging technologies. As technology is meant to help humanity, assistive technology relates well to those with special needs. In this paper, we present the structure of our device, highlighting on how the sensors were made. We also discuss the block level implementation of the gesture to speech translator and report a few results of our preliminary testing.